PERSPEKTIF FIKIH SIYASAH TERHADAP IMPLEMENTASI FUNGSI BADAN PERMUSYAWARATAN DESA: FIKIH SIYASAH'S PERSPECTIVE ON THE IMPLEMENTATION OF THE FUNCTIONS OF VILLAGE DEVELOPMENTAL BOARDS - Taufik, Muhammad; Haeruddin (Qaumiyyah: Jurnal Hukum Tata Negara, 2023)
This research specifically examines the Siyasah Jurisprudence Perspective on the Implementation of the Duties and Functions of the Village Consultative Body (study in Sarude Village, Sarjo District). This research aims to provide knowledge and understanding about the implementation of the duties and functions of the Village Consultative Body (BPD) in Sarude Village, Sarjo District. This research was designed using a type of empirical legal research that wanted to describe the process of the Siyasah Jurisprudence Perspective on the Implementation of the Duties and Functions of the Village Consultative Body (in Sarude Village, Sarjo District). The data collection techniques used in this research are observation, interviews, and documentation techniques. The results of this research show that the Implementation of the Duties and Functions of the Village Consultative Body (in Sarude Village, Sarjo Village), based on the results of research conducted by the author in the field, found several phenomena, such as a lack of village funds in terms of making village regulations or rules and in terms of monitoring, accommodating, and channeling community aspirations, running well. The conclusions from this research are: Implementation of the duties and functions of the Village Consultative Body (in Sarude Village, Sarjo District) has not been well implemented, especially in the field of making regulations with the Village Head. and as for the Siyasah Jurisprudence Perspective on the Implementation of the Duties and Functions of the Village Consultative Body (in Sarude Village, Sarjo District), namely that the BPD applies the principles of Siyasah Jurisprudence and as is done by Ahl al-hall wa al-aqd in Islam. Abstrak Penelitian ini secara spesifik mengkaji Perspektif Fikih Siyasah Terhadap Implementasi Tugas dan Fungsi Badan Permusyawaratan Desa (study di Desa Sarude Kecamatan Sarjo). Penelitian ini bertujuan untuk memberikan pengetahuan dan pemahaman tentang Implementasi Tugas dan Fungsi Badan Permusyawaratan Desa (BPD) di Desa Sarude Kecamatan Sarjo. Penelitian ini didesain dengan menggunakan jenis Penelitian hukum empiris yang hendak menggambarkan proses Perspektif Fikih Siyasah Terhadap Implementasi Tugas dan Fungsi Badan Permusyawaratan Desa (di Desa Sarude Kecamatan Sarjo). adapun tehnik pengumpulan data yang digunakan dalam penelitian ini adalah tehnik observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa Implementasi Tugas dan Fungsi Badan Permusyawaratan Desa (di Desa Sarude kacamatan Sarjo), berdasarkan hasil penelitian yang dilakukan penulis di lapangan menemukan beberapa fenomena seperti kurangnya dana Desa dalam hal pembuatan regulasi atau peraturan Desa, dan dari segi pengawasan, menampung dan menyalurkan aspirasi masyarakat, berjalan dengan baik. Adapun kesimpulan dari penelitian ini yaitu: Implementasi Tugas dan Fungsi Badan Permusyawaratan Desa (di Desa Sarude Kecamatan Sarjo), belum terlaksana dengan baik terutama dibidang pembuatan regulasi bersama Kepala Desa. dan adapun Perspektif Fikih Siyasah Terhadap Implementasi Tugas dan Fungsi Badan Permusyawaratan Desa (di Desa Sarude Keacamatan Sarjo) yaitu BPD menerapkan prinsip Fikih Siyasah dan seperti halnya yang dilakukan oleh Ahl al-hall wa al-aqd dalam Islam.